2010
DOI: 10.1016/j.jcrs.2010.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic correlation of capsulorhexis phimosis with anterior flexing of single-piece hydrophilic acrylic intraocular lens haptics

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 9 publications
0
18
0
2
Order By: Relevance
“…However, as stressed by Zaugg et al [23], Qatarneh et al [21] and by Caravella [20], we believe that, when CCS occurs with IOLs such as the Akreos MI60, which has to be particularly soft to enter the eye through a microincision, it easily causes compression stretching of the IOL, resulting in a significant dislocation and deformation of both the optics and the haptics.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…However, as stressed by Zaugg et al [23], Qatarneh et al [21] and by Caravella [20], we believe that, when CCS occurs with IOLs such as the Akreos MI60, which has to be particularly soft to enter the eye through a microincision, it easily causes compression stretching of the IOL, resulting in a significant dislocation and deformation of both the optics and the haptics.…”
Section: Discussionmentioning
confidence: 74%
“…Both patients developed CCS, which caused ciliary body detachment in the first patient (as reported by Lanzl [7], Salzman et al [8], and Srinivasan et al [10]) and posterior dislocation of the IOL optic in the latter (as reported by Sanders et al [14], Ozturk et al [16], Qatarneh et al [21], and Zaugg et al [23]) (table 1). Notwithstanding the fact that no ocular risk factors were apparently present (since surgery had been performed elsewhere), we cannot exclude a weakness of the zonular apparatus, even in the absence of pseudoexfoliation or a small capsulorhexis as intraoperative causative factors of CCS.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…High myopia · Single-piece intraocular lens · Three-piece intraocular lens · Refractive predictability · Stability de bei einigen Patienten mit einem ähn-lichen hydrophilen Acrylmaterial bereits beschrieben [12,19]. Klinisch signifikante Kapselschrumpfung oder Kapselphimosen wurden bei unseren Patienten aber nicht beobachtet.…”
Section: Introductionunclassified